(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2024)
This article explores the impact of film festivals’ retrospective programming on the canons of global art cinema, wanting to contribute to a current trend in film scholarship exploring the relationship between film festivals and film histories. The argument proposed here is that, by recircling and mediating the latest film restorations and even taking ownership of specific restoration initiatives, film festivals have become key platforms for the rediscovery of so-called ‘film classics’, thus crucially contributing to shape the articulations and understanding of film histories. To this aim, the article gauges with the dynamics of cinematic rediscoveries through the theoretical prism of cultural memory studies, exploring how film festivals developed, between the early 1980s and the 1990s, a retrospective interest in the material body of the film historical past, and its preservation and restoration,acting as both arbiters and harbingers of what body of films become available once again and, eventually, studied by scholars, critics and students. By considering several institutional cases and the emergence of retrospective strands in some of the major A-list festivals, this article contends that these festivals have become essential ‘sites of passage’ to the contemporary ways of accessing and historicizing of the histories of global art cinema.